2018
DOI: 10.1371/journal.pone.0203626
|View full text |Cite
|
Sign up to set email alerts
|

Modulating the antioxidant system by exogenous 2-(3,4-dichlorophenoxy) triethylamine in maize seedlings exposed to polyethylene glycol-simulated drought stress

Abstract: Maize (Zea mays L.), an important agricultural crop, suffers from drought stress frequently during its growth period, thus leading to a decline in yield. 2-(3,4-Dichlorophenoxy) triethylamine (DCPTA) regulates many aspects of plant development; however, its effects on crop stress tolerance are poorly understood. We pre-treated maize seedlings by adding DCPTA to a hydroponic solution and then subjected the seedlings to a drought condition [15% polyethylene glycol (PEG)-6000 treatment]. The activities of superox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 66 publications
(81 reference statements)
2
10
0
Order By: Relevance
“…In this study, the increased contents of total amino acids, serine, glycine, valine, isoleucine, leucine, tyrosine, lysine, histidine, methionine, and arginine and the decreased contents of soluble protein in seedlings exposed to PEG-simulated drought stress may have been due to the promotion of protein degradation and the suppression of protein biosynthesis by inadequate supplies of reducing potential (in the form of NADPH and ATP) due to reduced photosynthesis (Table 4, Figure 9) [62,63]. Exogenous DCPTA weakened these effects induced by PEG-simulated drought stress, which may be attributed to the alleviation of stress-induced photosynthetic inhibition and oxidative damage, as demonstrated in our previous studies [26,27].…”
Section: Discussionmentioning
confidence: 54%
See 3 more Smart Citations
“…In this study, the increased contents of total amino acids, serine, glycine, valine, isoleucine, leucine, tyrosine, lysine, histidine, methionine, and arginine and the decreased contents of soluble protein in seedlings exposed to PEG-simulated drought stress may have been due to the promotion of protein degradation and the suppression of protein biosynthesis by inadequate supplies of reducing potential (in the form of NADPH and ATP) due to reduced photosynthesis (Table 4, Figure 9) [62,63]. Exogenous DCPTA weakened these effects induced by PEG-simulated drought stress, which may be attributed to the alleviation of stress-induced photosynthetic inhibition and oxidative damage, as demonstrated in our previous studies [26,27].…”
Section: Discussionmentioning
confidence: 54%
“…In our previously reported results, DCPTA was proven to increase the drought tolerance of maize seedlings under hydroponic conditions [26,27]. However, the underlying molecular mechanisms remain poorly understood.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Our previous hydroponic trial found that exogenous DCPTA drastically promoted growth under non-stress conditions and mitigated the PEG-simulated drought-induced growth inhibition of maize at the seedling stage by improving photosynthetic capacity [20] and modulating antioxidant system [21]. The present study was conducted to explore whether DCPTA can alleviate soil drought injuries to maize and whether the effects are associated with the modulation of N metabolism.…”
Section: Introductionmentioning
confidence: 99%